Analyzing the Use of Conjunctions in the Articles Published in Wired Magazine - Septiani, Sabrina Dwi; Sulyaningsih, Iis; Ridhawati, Listya Arum (Jurusan Bahasa Inggris - Politeknik Negeri Bandung, 2025)
The use of conjunctions is important to create cohesiveness and also enhance coherence to the text or article that make the readers ease to understand the idea of the text/article. Furthermore, the careful application of conjunctions enhances readability and expresses the meaning effectively. Thus, understanding the use of conjunctions is essential for clear understanding and comprehension. However, EFL (English as Foreign Language) learners, especially in Indonesia, still struggle with the use of proper conjunctions. This study focused on analyzing the use of conjunctions in the articles published in Wired Magazine. This aimed to show how conjunctions are used in texts, especially text in magazines. This study used qualitative method and which focused on four types of conjunctions: coordinating, subordinating, correlative, and conjunctive. The result showed 614 conjunctions were found includes 410 coordinating conjunctions, 159 subordinating conjunctions, 34 conjunctive conjunctions, and 11 correlative conjunctions. The data showed that coordinating conjunction is the most frequently used conjunction.